Modelo hidrológico de grande escala aplicado a bacia do Rio Uruguai - Cardoso, Guilherme Jordão (2022)
The use of computational tools to represent the hydrological cycle, and to analyze its characteristics to understand the behavior behind its changes has been a difficult task, since the environment is always changing, either by anthropic actions or by new climatic periods. The several variables to be inserted in a model that can represent, understand and predict the hydrological functioning of a large hydrographic basin is a challenge that can only be overcome with the support of hydrological-hydrodynamic simulation models, which take into account the various factors that influence a given hydrographic region and can adequately represent the environment in question. Hydrological forecasting and monitoring systems are still based on models that only analyze hydrological data without combining them with the environment, without evaluating conditions that interfere with flow, runoff, precipitation, soil infiltration, evaporation. and transpiration of water bodies and in works such as dams and hydroelectric plants that alter the water regimes of water bodies. Therefore, the present work aims to evaluate and predict the hydrological functioning of large hydrographic basins, supported by hydrological-hydrodynamic simulation models, evaluating the main hydrological models for application in large hydrographic basins. The main models were evaluated within studies that approached different types, and through this bibliographic search, the best models for a flood forecasting system for the Uruguay basin, being chosen the MGB-IPH model for application testing and verification of the tools. of calibration. The GIS database for the study was prepared with the data available for the region of the hydrographic basin, and then the pre-processing of preliminary geographic information was carried out so that it can be applied to the Uruguay River basin. The results show that the most important parameters for the runoff sections were those linked to vegetation and land use, and for sub-surface runoff and infiltration according to the type of soil. The parameters stipulated by manual calibration with those optimized by the automatic calibration tool of the model, there are values for the coefficients above 0.7 and volumetric errors within the range of amplitude from five to minus five, having adjusted the calibratable parameters in 65 sub-basins of the Uruguay River. The model used showed good results for predicting behavior in the basin, but requires the user to have a prior knowledge of the basin and the functioning of the model. Thus, the model can be a good option for predicting the behavior of large watersheds.